2021
DOI: 10.51470/plantarchives.2021.v21.no1.148
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Pteridophytes in Western Ghats- A Review

Abstract: Pteridophytes are vascular cryptogams that dominated the earth 250 million years ago. Currently, there are 13,600 species of pteridophytes around the world, and is the second most dominant plant group. In India, there are 1200 pteridophyte species with 70 families and 192 genera. The pteridophyte hotspots in India are the Himalayas, Western Ghats, Eastern Ghats, Central India, and Andaman and the Nicobar Islands. The Western Ghats occupies only 6% of the Indian landmass and still holds a pteridophyte diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition, these conditions greatly affect the distribution of pteridophytes to be higher and wider. Previous studies also reported that tropical rainforests had a very high diversity and abundance of plants, especially pteridophytes (Baraloto et al 2013;Haque et al 2016;Krishnan and Rekha 2021). In contrast, the Cendil heath forest had habitat characteristics that were inversely proportional to the Gurok Beraye tropical rainforest.…”
Section: Environmental Variables Of Pteridophyte's Habitatmentioning
confidence: 91%
“…In addition, these conditions greatly affect the distribution of pteridophytes to be higher and wider. Previous studies also reported that tropical rainforests had a very high diversity and abundance of plants, especially pteridophytes (Baraloto et al 2013;Haque et al 2016;Krishnan and Rekha 2021). In contrast, the Cendil heath forest had habitat characteristics that were inversely proportional to the Gurok Beraye tropical rainforest.…”
Section: Environmental Variables Of Pteridophyte's Habitatmentioning
confidence: 91%